Comparism Between Gunungsitoli and Teluk Dalam Dialect in Nias District - Mac Aditiawarman; Herfanus Duha Herfanus Duha (Jurnal Ilmiah Langue and Parole, 2026)
This research entitled Comparison between Gunungsitoli and Teluk Dalam dialects in Nias Regency: Social Dialect Study aims to analyze the similarities, changes and differences in lexical forms and to determine the matrix language in the use of the Nias language along with the levels of speech used by the Gunungsitoli and Teluk Dalam communities, especially in the Nias communities in Lubuk Buaya and Pasar Obsolete. The method used in this study is qualitative and quantitative with a descriptive type, namely describing the form and shape and calculating the percentage comparison between the Gunungsitoli and Teluk Dalam dialects obtained from the results of interview data transcription. The data obtained are in the form of Nias dialect vocabulary. The data collection technique used is the observation technique using the interview method then transcription is carried out, so that the data can be analyzed according to the research instrument. The theory used in this study is the theory of lexical, dialect and matrix language. The results of the analysis indicate that GN is the dominant dialect (ML) and TD is a contributing dialect (EL) with a percentage level in the lexicon of the same form and the same meaning at 61.69%; lexical form changes meaning is the same in 8.65%; and lexical form different meaning is the same in 28.5% between GN and TD. The existence of similarities, changes and differences in form between Gunugsitoli and Teluk Dalam dialects in Nias is caused by geographical conditions which are the main cause.